Some Economic Indicators of The Current Situation of Food Vegetable Oils in Egypt and Its Future Prospects - El-Elsharkasy, Shaker; Meky, Fouad Mohamed Hafeez; Al-Tarawi, Abdel-Sattar Abdel Hamid; Abosalem, Ali Saad Elsayed; El-Megeed, Mohamed Ashraf Abd El-Malek Abd; Srour, Ahmed Hassan (Advances in Social Sciences Research Journal, 2023)
Vegetable oils are considered daily basic food commodities, and Egypt is considered one of the largest importing countries in general. The food gap of food vegetable oils increases in Egypt due to the population increase, as well as the increase in individual consumption rates of food oils, and the lack of cultivated areas with oil food crops. The research aimed to identify the oil food gap, and the study relied on the method of statistical and quantitative analysis represented in the equations of the general time trend and choosing the best of them according to economic and statistical logic. The research concluded that one of the most important dietary oil crops are crops (soybeans, cottonseeds, sunflower, maize oil, and other oils). By studying the total average production of these crops during the period (2000-2019), it amounted to about 107.2, 44.74, 16.89, 11.47, and 10.58 thousand tons, respectively. 9.01, 38.58 thousand tons, respectively. The research also dealt with the development of the consumption capacity of food vegetable oils during the period (2000-2019), as well as the development of individual consumption of food vegetable oils, the oil food gap, the development of the self-sufficiency rate of food vegetable oils, and some factors that lead to a reduction of the size of the oily food gap, By studying some indicators of food security for edible oils in Egypt, it became clear that the population of Egypt during the average period amounted to about 79.56 million people, and a statistically significant annual increase is increasing by about 1.77 million people. As for the total average production, it amounted to about 202.3 thousand tons, and it increases annually by about 2.03. thousand tons, while the average imports of edible vegetable oils amounted to about 968 thousand tons, and it increases annually by about 54.51 thousand tons, and this increase is statistically significant. As for the average size of the oil gap, it amounted to about 814.2 thousand tons, and it increases annually by about 32.79 thousand tons. This increase is statistically significant. The average of self-sufficiency rate reached about 23.21%, and the average per capita share of food vegetable oils reached about 14.42 (kg/year), while the development of the average per capita consumption of food vegetable oils (calories / day) at the level of the Republic reached about 324. 74 (calories /day) and it is increasing daily by about 8.32 (calories /day). As for the development of the average per capita consumption of food vegetable oil protein (grams/day) in Egypt, it amounted to about 35.20 (grams/day), and it is expected that the average of population, total production, imports, available for consumption, size of the oil gap, self-sufficiency rate, average per capita consumption during the average period (2023-2027) about 108.87 million people, 231.41 thousand tons, 1840.80 thousand tons, 2072.21 thousand tons, 1272.76 thousand tons , 15.75%, 20.07 (kg/year), 453.37 calories, 48.52 grams of fat, respectively.